(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The mathematical model for calculating the flow rate of fluids when dispersed from nozzles is based on the principles of fluid mechanics, using equations for the velocity of the fluid and the effects of nozzle diameter, pressure, and the dynamic properties of the fluid (density, viscosity). The model includes calculations of the flow rate based on the theoretical exit velocity from the nozzle, along with corrections for pressure losses associated with friction and turbulence. The Reynolds number is used to assess the flow characteristics (laminar or turbulent), which is crucial for optimizing the fluid dispersion. In MATLAB, various plots are generated to show the dependencies between the flow rate, nozzle diameter, and pressure, enabling a deeper understanding of the fluid behaviour during dispersion. The model is applicable to different types of fluids, including solutions with surfactants and hypochlorites, used for disinfection purposes.